Efikasi Diri Bahasa Inggris sebagai Mediator antara Orientasi Tujuan Penguasaan dan Keterikatan Siswa Belajar Bahasa Inggris - Andrielina Firdausih; Bhina Patria (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
English Self-efficacy is a self-confidence in English proficiency which is important to student behaviour on learning process. This study aimed to investigated the role of English self efficacy in mediating the relationship between mastery goal orientation and student engagement on learning English. The method was quantitative using survey approach with 173 subjects. The subjects were high school students of 10th and 11st grades selected by purposive sampling technique. The Morgan-Jinks Student Efficacy State modification scale, student engagement modification scale, and mastery goal orientation scale were used in this study. The result showed that English self-efficacy was partially mediated. The mastery goal orientation had direct positive role to the student engagement (B = 0.468; p < 0.001). The mastery goal orientation had positive role to the student engagement on learning English with self-efficacy as mediator (B’ = 0.369; p < 0.001), English self-efficacy on boys was higher than girls.